2017
DOI: 10.1016/j.bbr.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Reversal learning in C58 mice: Modeling higher order repetitive behavior

Abstract: Restricted, repetitive behaviors are diagnostic for autism and prevalent in other neurodevelopmental disorders. These behaviors cluster as repetitive sensory-motor behaviors and behaviors reflecting resistance to change. The C58 mouse strain is a promising model for these behaviors as it emits high rates of aberrant repetitive sensory-motor behaviors. The purpose of the present study was to extend characterization of the C58 model to resistance to change. This was done by comparing C58 to C57BL/6 mice on a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 33 publications
4
26
1
Order By: Relevance
“…These behaviors are expressed at or before weaning, persist throughout development and are readily observed throughout the dark cycle in both the home cage and individual test cages . Moreover, we have shown that C58 mice exhibit a pronounced resistance to change or behavioral inflexibility in a reversal learning task . We have also shown that rearing C58 mice in environmental enrichment (EE) for 6 weeks starting at weaning (postnatal day [PND] 21) dramatically reduced repetitive motor behaviors compared with littermates reared in standard cages and improved reversal learning …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These behaviors are expressed at or before weaning, persist throughout development and are readily observed throughout the dark cycle in both the home cage and individual test cages . Moreover, we have shown that C58 mice exhibit a pronounced resistance to change or behavioral inflexibility in a reversal learning task . We have also shown that rearing C58 mice in environmental enrichment (EE) for 6 weeks starting at weaning (postnatal day [PND] 21) dramatically reduced repetitive motor behaviors compared with littermates reared in standard cages and improved reversal learning …”
Section: Introductionmentioning
confidence: 99%
“…17,19 Moreover, we have shown that C58 mice exhibit a pronounced resistance to change or behavioral inflexibility in a reversal learning task. 20 We have also shown that rearing C58 mice in environmental enrichment (EE) for 6 weeks starting at weaning (postnatal day [PND] 21) dramatically reduced repetitive motor behaviors compared with littermates reared in standard cages 17 and improved reversal learning. 20 Excessive self-grooming behavior is a common repetitive behavior in mouse models of psychiatric and neurodevelopmental disorders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature demonstrates that response blocking (i.e., extinction; Wolff, Hupp, & Symons, 2013), differential reinforcement of alternative behaviors (DRA) with extinction (Fisher et al, 2013), and functional communication training with extinction (Rispoli et al, 2014) are all effective ways of treating higher-order restricted and repetitive behaviors. Given the well-supported distinction between lower-and higher-order restricted and repetitive behaviors, it is important to more fully evaluate the effects of behavioral interventions with and without extinction on individuals' resistance to change (Whitehouse, Curry-Pochy, Shafer, Rudy, & Lewis, 2017).…”
mentioning
confidence: 99%
“…Several studies revealed that C58/J mice displayed increased activity and repetitive behaviors, as well as less social approach in the three-chamber test [48][49][50][51] . Environmental enrichment (rearing in enriched cages) was reported to reduce repetitive behaviors and improve reversal learning in this strain [52,53] .…”
Section: Effect Of Environmental Enrichment On Inbred Mouse Models Ofmentioning
confidence: 94%